The association of parental smoking and infant birth weight among women who delivered in the Philippine General Hospital maternity ward - Kol Hero
A cross-sectional study was conducted from October 20, 1997 to January 9, 1998 to find out the association between parental smoking status and infant birth weight. Six hundred and fifty three pregnant women who delivered a single baby in the Philippine General Hospital were included in the study. Data were collected using the interview of mother, husband or relatives who agreed to participate in the study. Simple analysis included generation of two-way tabulation and computation of odds ratios and confidence intervals. Stratified analysis and logistic regression were used to control for possible confounders. The results showed that the association between low birth weight of infants and active maternal smoking was statistically significant but not with passive smoking of mothers. Simultaneously controlled on extraneous variables by using multiple logistic regression. This study revealed that the adjusted prevalence odds ratio of low birth weight of infants among active smoking of mothers during pregnancy was 6.5 times higher than non-smoking mothers. Based on these results, the campaign to stop maternal smoking should be intensified to prevent low birth weight among infants of smoking mothers.